2019
DOI: 10.14569/ijacsa.2019.0100203
|View full text |Cite
|
Sign up to set email alerts
|

Smart Building’s Elevator with Intelligent Control Algorithm based on Bayesian Networks

Abstract: Implementation of the intelligent elevator control systems based on machine-learning algorithms should play an important role in our effort to improve the sustainability and convenience of multi-floor buildings. Traditional elevator control algorithms are not capable of operating efficiently in the presence of uncertainty caused by random flow of people. As opposed to conventional elevator control approach, the proposed algorithm utilizes the information about passenger group sizes and their waiting time, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…The results demonstrated that the suggested algorithm demonstrated the intended behaviour in 94% of the circumstances examined. [8] Z. Yang and W. Yue investigated Elevator Traffic Pattern Recognition Using Fuzzy BP Neural Network with Self-Organizing Map (SOM) Algorithm in 2017. SOM is a form of unsupervised learning network method that operates on the premise of grouping comparable inputs on the same output in order to find a better clustering centre after a sufficient number of repetitions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results demonstrated that the suggested algorithm demonstrated the intended behaviour in 94% of the circumstances examined. [8] Z. Yang and W. Yue investigated Elevator Traffic Pattern Recognition Using Fuzzy BP Neural Network with Self-Organizing Map (SOM) Algorithm in 2017. SOM is a form of unsupervised learning network method that operates on the premise of grouping comparable inputs on the same output in order to find a better clustering centre after a sufficient number of repetitions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BNs have already been used in a variety of different engineering fields (Bapin and Zarikas, 2019a;Amrin et al, 2018;Zarikas et al, 2018;Papanikolaou et al, 2017;Zarikas et al, 2015;Zarikas et al, 2013;Zarikas, 2007;Stephanidis et al, 2005;Yang et al, 2019;Gao and Dong, 2019;Jha et al, 2019;Tselykh et al, 2018;Nakasima-L opez et al, 2018;Ung, 2018;Quinn et al, 2017;Yang and Xu, 2017;Sanchez et al, 2017), yet only a few works use BNs for the power system reliability assessment or probabilistic quantification of power generating reserve capacity. Yu et al (1999) is one of the first works, which uses BNs to evaluate reliability of a power grid.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest works describing utilization of video cameras in conventional passenger elevators was presented in a paper by [4]. The study is limited to the people-counting problem and is not intended to address elevator control optimization.…”
Section: Introductionmentioning
confidence: 99%